Yield of Larix sukaczewii Dyl. in northern Sweden - Martinsson, Owe (1995)
The stem volume yield of twenty small stands of larch, mainly Larix sukaczewii Dyl., was studied in northern Sweden. The stand age range was 34-89 years. On the most productive sites trees attain a dominant height of 27 m at age 60 years. Tree height increment is still continuing at age 90 years. The productivity of larch varies widely, depending on site quality. During a 100-year rotation, the total volume yield of larch on medium sites was calculated at 500 m3 ha-', and at 1000 m3 ha-' on the most productive sites (both including bark). On the most productive sites, stem volume yield of larch exceeded that of indigenous conifers by 10-25 per cent (excluding bark). On poor, dry, flat or waterlogged sites the yield of larch was inferior to that of indigenous conifers. On high-altitude sites, surprisingly high yields were observed.